Identification and Genetic Diversity of Pineapple Local Accessions from Kediri and Closely Related Species (Bromeliaceae) Based on matK Gene - Rasyadan Taufiq Probojati; Hadiyanti, Nugraheni; Hapsari, Lia (Universitas Brawijaya, 2024)
Ananas comosus L. belongs to the Bromeliaceae family and has around eight subfamilies. Accessions of local pineapple have spread widely in several areas, one of which is in Kediri. However, some accessions and closely related species (Bromeliaceae) likely remain poorly understood relationships. The highly diverse morphological characters and low levels of sequence divergence in Bromeliaceae have been problematic in resolving the reconstruction of phylogenetic relationships. This study aimed to evaluate the efficiency of the matK gene as a DNA barcode to determine genetic diversity and reconstruct a phylogenetic tree in local pineapple and closely related species (Bromeliaceae). A total of 15 specimens were used in this research, of which 7 were local pineapple accessions from Kediri and eight were closely related species from the Bromeliaceae family. Whole genome DNA was isolated using a Tiangen kit and amplified using the polymerase chain reaction (PCR) technique using a specific primer. The results showed that matK was easily amplified with a DNA fragment length of 750-800 bp. The average composition value of each base was 36.9% T (U) bases, 30.1% in A bases, 15.9% in G bases, and 17.1% in C. BLAST analysis of the sequences showed that all samples were confirmed and identified according to the species names spread across local pineapple production areas (with query cover of 96-98%). However, the species names registered in the PBG database were confirmed to be different species but still in the same genus, i.e., samples B9-B14. The phylogenetic relationship analysis distinguished each accession into two large clades according to sub-families, i.e., Bromelioideae and Pitcairnioideae. This research shows that the matK gene is suitable and recommended as a DNA barcode for local pineapple and closely related species.